Pengaruh Promosi dan Persepsi Wisatawan terhadap Intensitas Penggunaan Platform Viator pada PT Wahyu Mandiri Tour - Ni Kadek Dwi Puspawati Purna; Ni Nyoman Teristiyani Winaya; Wayan Gede Suka Parwita (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The rapid growth of Online Travel Agencies (OTAs) has encouraged tourism businesses to adopt digital platforms as an effective marketing channel. This study aims to examine the influence of promotion and tourist perception on the intensity of Viator platform usage at PT Wahyu Mandiri Tour. A quantitative approach with a causal research design was employed. The study involved 100 tourists who had previously made bookings through the Viator platform, selected using a purposive sampling technique. Data were collected through a structured Likert-scale questionnaire and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with IBM SPSS. The findings reveal that promotion has a positive and significant influence on the intensity of Viator platform usage (β = 0.453, p < 0.001). Tourist perception also demonstrates a positive and significant effect (β = 0.456, p < 0.001) and emerges as the more dominant predictor. Furthermore, promotion and tourist perception jointly exert a significant influence on the intensity of platform usage (F = 371.369, p < 0.001). The regression model explains 88.2% of the variance in platform usage intensity (Adjusted R² = 0.882), indicating strong explanatory power. These findings suggest that sustained use of the Viator platform depends not only on effective promotional strategies but also on tourists' positive perceptions regarding platform usability, trustworthiness, service quality, and perceived benefits. Strengthening these factors is therefore essential for enhancing long-term user engagement and supporting the digital marketing performance of tourism businesses.